INOVASI PELAYANAN PUBLIK DALAM PENANGGULANGAN KEMISKINAN - Arif Sofianto; Kissumi Diyanayati; Sadiman Al Kundarto (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2014)
Poverty is a major problem in developing countries who need to unified and systematic treatment. Sragen Regency has the initiative to develop an integrated model of social services to the poor with Integrated Service Unit for Poverty Reduction (UPTPK). The purpose of this study is: 1). Describe the implementation UPTPK in Sragen Regency, and 2). Analyzing prospects and strategies UPTPK replication in other areas. This study is a descriptive research, the analysis technique used is an interactive model of Miles and Huberman. The conclusion of this study are: 1). Implementation UPTPK in Sragen Regency is good enough, the drawback is that the institutional forms that do not have a strong legal basis and is still a lack of planning services. 2). Possible replication in other areas if there is a strong commitment from the head area and the support of the Central Government and the Provincial Government.